Conformational states of cytochrome P450 oxidoreductase evaluated by FRET using ultrafast transient absorption spectroscopy - Kovrigina, Elizaveta A (Biochemistry, 2016)
NADPH-cytochrome P450 oxidoreductase (CYPOR) was demonstrated to undergo large conformational rearrangements in its functional cycle. Using a new FRET approach based on femtosecond transient absorption spectroscopy (TA), we determined the donor-acceptor distance distribution in the reduced and oxidized states of CYPOR. Unmatched time resolution of TA enabled the quantitative assessment of the donor-acceptor FRET indicating that CYPOR assumes a closed conformation in both reduced and oxidized states in the absence of the redox partner. The described ultrafast TA measurements of FRET with readily available red-infrared fluorescent labels open new opportunities for structural studies in chromophore-rich proteins and their complexes.